Distribution Of Dengue Hemorrhagic Fever (DBD) Incidence In Jambi City - Fajrina Hidayati; Andree Aulia Rahmat; Adila Solida; Evy Wisudariani; Fitria Eka Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that is influenced by the environment and people's behavior. In Jambi City, Dengue Fever is still a public health problem. This research aims to distribute dengue hemorrhagic fever (DBD) incidence in Jambi City. This research uses Global Moran's analysis and Local Indicator of Spatial Association (LISA) to determine the Hot Spot and Cold Spot areas for dengue cases in Jambi City in 2018 -2022 with a sub-district analysis unit of 62 sub-districts. During 5 years of observation, the results showed that the distribution pattern of dengue fever cases was in the form of a clustered pattern (I>E[I]) in 2018-2022. The research results on the distribution of dengue fever cases from 2018-2022 showed that the lowest cases were in 2021, namely 132 cases, while the highest cases were in 2019, 698 cases. The results of this study are expected to provide an overview of the distribution of dengue fever incidence in Jambi City in 2018 - 2022 so that it becomes a recommendation material for the Jambi City Health Office or the Jambi City Government in an overview of environmental factors related to dengue fever incidence in Jambi City to prevent various diseases due to poor environmental sanitation in Jambi City. Knowing the distribution pattern of dengue fever can determine regional priorities in implementing dengue fever prevention and control intervention programs in Jambi City.